1997
DOI: 10.1016/s0925-4773(97)00668-0
|View full text |Cite
|
Sign up to set email alerts
|

Camguk, Lin-2, and CASK: novel membrane-associated guanylate kinase homologs that also contain CaM kinase domains

Abstract: MAGUKs (membrane-associated guanylate kinase homologs) are proteins involved in cell junction organization, tumor suppression, and signalling. Their structure includes one or three copies of a DHR or PDZ domain (discs-large homologous region or PSD-95/SAP90, discs-large ZO-1 homologous domain), an SH3 domain, and a guanylate kinase domain. MAGUKs were classified into two subfamilies: Dlg-like with three DHR/PDZ domains and p55-like with a single DHR/PDZ domain. There is now a new subfamily whose members have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 9 publications
0
40
0
2
Order By: Relevance
“…Membrane-associated guanylate kinase proteins (MAGUKs) form the most prominent family of scaffolding molecules associated with intercellular junctions. MAGUKs are characterized by three canonical domains: N-terminal PDZ domains, a central SH3 domain, and a C-terminal guanylate kinase domain (1,2). A large number of MAGUKs with these domains were described, but CASK is the only MAGUK that contains an additional large N-terminal domain with homology to calcium/ calmodulin-dependent protein kinase II␣ (3).…”
mentioning
confidence: 99%
“…Membrane-associated guanylate kinase proteins (MAGUKs) form the most prominent family of scaffolding molecules associated with intercellular junctions. MAGUKs are characterized by three canonical domains: N-terminal PDZ domains, a central SH3 domain, and a C-terminal guanylate kinase domain (1,2). A large number of MAGUKs with these domains were described, but CASK is the only MAGUK that contains an additional large N-terminal domain with homology to calcium/ calmodulin-dependent protein kinase II␣ (3).…”
mentioning
confidence: 99%
“…CASK was originally identified as a neurexin-interacting partner in rat brain [2]. CASK is a membrane-associated guanylate kinase protein (MAGUK) [3] and regulates lineage-specific decisions in a variety of taxa, including nematodes and mammals [4,5]. CASK is considered to be a pseudokinase because the functionally important residues within CaMKII domain are mutated [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sera were screened against the antigens in ELISAs and in Western blots of purified N-or C-terminal EAG fragments as appropriate. Purified GST-CMG 152-897 was used for the immunization of guinea pigs as described previously (Dimitratos et al, 1997). Phosphospecific anti-EAG antibody was a gift from Leslie Griffith (Brandeis University, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has demonstrated that Drosophila CaMKII interacts with the Camguk (CMG) adaptor protein (Lu et al, 2003). CMG is a member of the membrane-associated guanylate kinase (MAGUK) family of adaptor proteins and the Drosophila ortholog of CASK and Lin-2 (Hata et al, 1996;Hoskins et al, 1996;Dimitratos et al, 1997;Butz et al, 1998). CMG/CASK/ LIN-2 is unique in that the N terminal (NT) displays considerable homology to CaMKII.…”
Section: Introductionmentioning
confidence: 99%